Conflict or Collaboration—The Impact of Knowledge Endowment Heterogeneity on Remix in Open Collaborative Communities - Tan, Juan; Qi, Congcong; Gao, Xiaohui; Lu, Jianle; Tan, Qiong (Frontiers in Psychology, 2022)
With the emergence of online open platforms and communities, remix has drawn much attention as an essential source of innovation whereby the knowledge endowment of online community users plays a crucial role. This study constructs a structural equation model to explore the impact of user knowledge endowment heterogeneity on remix through the mediating effect of their collaborative psychology. In this empirical study, we collected 25,032 pieces of data from Thingiverse (a 3D printing community) users and their published designs. The findings are as follows. Explicit knowledge endowment heterogeneity has a positive impact on the quantity of remix but a negative impact on its quality. Likewise, the implicit knowledge endowment heterogeneity positively affects the quantity of remix but has no significant effect on its quality. Users’ conflicting psychology plays a mediating role between knowledge endowment heterogeneity and remix, while their collaborative psychology negatively mediates merely between explicit knowledge endowment heterogeneity and remix quality. By unraveling the relationship between user knowledge endowment heterogeneity, collaborative psychology, and remix, this study is significant in understanding users’ remix process in open collaborative communities and illuminating their psychological mechanism in this process.